An antistatic high-barrier polymer film and its application in semiconductor packaging

Functionalized cyclic carbonate is prepared by reacting epoxidized phenylphosphate with carbon dioxide, and polyurethane is prepared by reacting with 1,6-hexanediamine, and then anti-static high-barrier polymer film is prepared by calendering with modified nanomontmorillonite and blocked isocyanate crosslinking agent. This solves the problem that existing polymer films are prone to friction and electricity in semiconductor packaging, and achieves excellent anti-static, mechanical, flame retardant and barrier properties.

CN118206863BActive Publication Date: 2025-04-18JIANGSU PUQING PURIFICATION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410297464.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2025-04-18
Estimated Expiration
2044-03-14

AI Technical Summary

Technical Problem

Existing polymer films are prone to friction and electricity in semiconductor packaging, which affects the service life and performance of semiconductors and lacks anti-static and high barrier properties.

Method used

Functionalized cyclic carbonate is prepared by reacting epoxidized phenylphosphate with carbon dioxide, and polyurethane is prepared by reacting with 1,6-hexanediamine, and then an anti-static high-barrier polymer film is prepared by calendering with modified nanomontmorillonite and blocked isocyanate crosslinking agent.

Benefits of technology

It achieves excellent anti-static and mechanical properties of polymer films, while also imparting good flame retardant and barrier properties, extending the service life of semiconductors and improving their performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0004742724020000031
    Figure BDA0004742724020000031
Patent Text Reader

Abstract

The invention discloses an antistatic high-barrier polymer film and its application in semiconductor packaging, and relates to the technical field of polymer materials. When preparing the antistatic high-barrier polymer film, the present invention first oxidizes and polymerizes 3,4-ethylenedioxythiophene and 3-thiophene methanol and deposits them on nano-montmorillonite to obtain modified nano-montmorillonite; phenyl dichlorophosphate is reacted with glycidol to obtain epoxidized phenyl phosphate; epoxidized phenyl phosphate is reacted with carbon dioxide to obtain functionalized cyclic carbonate; functionalized cyclic carbonate is reacted with 1,6-hexamethylenediamine to obtain polyurethane; polyurethane, modified nano-montmorillonite, and blocked isocyanate crosslinking agent are calendered to obtain an antistatic high-barrier polymer film. The antistatic high-barrier polymer film prepared by the present invention has excellent antistatic, high-barrier, flame-retardant and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, in particular to an antistatic high-barrier polymer film and application thereof in semiconductor packaging. Background Art

[0002] Semiconductors refer to materials with electrical conductivity between conductors and insulators at room temperature. They can be divided into elemental semiconductors, inorganic composite semiconductors, organic composite semiconductors, amorphous semiconductors, and intrinsic semiconductors. They have important applications in integrated circuits, consumer electronics, communication systems, photovoltaic power generation, lighting, high-power power conversion, and other fields. Whether from the perspective of science and technology or economic development, the use of semiconductors is very important.

[0003] During the production, transportation and use of semiconductors, polymer films are usually used to encapsulate them to play a role in corrosion prevention and protection. Polymer films usually have good electrical insulation properties, but if the resistance value is too high, it is easy to generate friction electrification, which affects the service life and performance of the semiconductor. Therefore, it is very necessary to develop a polymer film with antistatic and high barrier properties for use in semiconductor packaging. Summary of the invention

[0004] The object of the present invention is to provide an antistatic high-barrier polymer film and its application in semiconductor packaging to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The invention discloses an antistatic high-barrier polymer film. The antistatic high-barrier polymer film is prepared by reacting epoxidized phenyl phosphate with carbon dioxide to obtain functionalized cyclic carbonate; reacting the functionalized cyclic carbonate with 1,6-hexamethylenediamine to obtain polyurethane; and calendering the polyurethane, modified nano-montmorillonite and a blocked isocyanate crosslinking agent to obtain the film.

[0007] As an optimization, the modified nano-montmorillonite is prepared by oxidative polymerization of 3,4-ethylenedioxythiophene and 3-thiophene carbinol and depositing the 3,4-ethylenedioxythiophene and 3-thiophene carbinol on the nano-montmorillonite.

[0008] As an optimization, the epoxidized phenyl phosphate is prepared by reacting phenyl dichlorophosphate with glycidol.

[0009] As an optimization, the model of the blocked isocyanate cross-linking agent is VESTAGON B1530.

[0010] As an optimization, the preparation method of the antistatic high barrier polymer film includes the following preparation steps:

[0011] (1) Nano-montmorillonite, anhydrous ferric chloride and tetrahydrofuran are mixed uniformly in a mass ratio of 1: (0.03-0.05): (8-10), and ultrasonically treated for 1-2 hours to prepare a mixed solution; 3,4-ethylenedioxythiophene, 3-thiophene methanol, sodium dodecyl sulfate and deionized water are mixed uniformly in a mass ratio of 1: (0.1-0.2): (2-3): (6-8) to prepare a monomer solution; under the stirring conditions of 20-30° C. and 300-500 r / min, a monomer solution of 1-1.2 times the mass of the mixed solution is uniformly added dropwise to the mixed solution within 30 minutes, the temperature is raised to 45-55° C., the stirring reaction is continued for 20-24 hours, the mixture is filtered, and the mixture is washed with anhydrous ethanol and deionized water for 3-5 times each, and the mixture is dried at 5-10 Pa and 50-60° C. for 5-7 hours to obtain a modified nano-montmorillonite;

[0012] (2) Phenyl dichlorophosphate, triethylamine, and tetrahydrofuran are mixed uniformly in a mass ratio of 1: (0.1-0.2): (8-10), and glycidol 2-2.2 times the molar amount of phenyl dichlorophosphate is added dropwise at a uniform rate within 30 minutes at 0-2°C and 300-500 r / min under a nitrogen atmosphere, the temperature is raised to 20-30°C, the stirring reaction is continued for 7-9 hours, the mixture is filtered, and the mixture is dried at 50-60°C at 5-10 Pa for 5-7 hours to obtain epoxidized phenyl phosphate; epoxidized phenyl phosphate and tetrabutylammonium bromide are mixed uniformly in a mass ratio of 1: (0.01-0.03), the mixture is placed in a high-pressure reactor, carbon dioxide gas is introduced to maintain the pressure at 1.0-1.2 MPa, the mixture is stirred at 95-105°C and 300-500 r / min for 4-6 hours, and the mixture is cooled to room temperature to obtain a functionalized cyclic carbonate;

[0013] (3) adding the functionalized cyclic carbonate and 1,6-hexanediamine to N,N-dimethylformamide (10 to 12 times the mass of the functionalized cyclic carbonate) at a molar ratio of cyclic carbonate group to amino group of 1:1, adding 1,5,7-triazabicyclo[4.4.0]dec-5-ene (0.02 to 0.04 times the mass of the functionalized cyclic carbonate), stirring and reacting at 135 to 145° C. and 300 to 500 r / min for 22 to 24 hours under nitrogen protection, and drying at 5 to 7 Pa and 50 to 60° C. for 4 to 6 hours to obtain a polyurethane. ; Mix polyurethane, modified nano-montmorillonite and blocked isocyanate cross-linking agent in a mass ratio of 1: (0.05-0.07): (0.2-0.3), place in a hot melt machine, stir at 180-190°C and 300-500r / min for 10-20min, and then send to a calender for calendering. Set the calender temperature to 150-160°C, the calendering speed to 50-60m / min, the pressure to 24-30MPa, and let it stand for 5-6h to obtain an antistatic high-barrier polymer film.

[0014] As an optimization, the reaction process of the functionalized cyclic carbonate in step (2) is as follows:

[0015]

[0016] As an optimization, the reaction process of the polyurethane in step (3) is as follows:

[0017]

[0018] The invention discloses an application of an antistatic high-barrier polymer film in semiconductor packaging.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] When preparing the antistatic high-barrier polymer film, the present invention firstly carries out oxidative polymerization of 3,4-ethylenedioxythiophene and 3-thiophene carbinol and deposits them on nano-montmorillonite to obtain modified nano-montmorillonite; phenyl dichlorophosphate is reacted with glycidol to obtain epoxidized phenyl phosphate; epoxidized phenyl phosphate is reacted with carbon dioxide to obtain functionalized cyclic carbonate; functionalized cyclic carbonate is reacted with 1,6-hexamethylenediamine to obtain polyurethane; polyurethane, modified nano-montmorillonite and a blocked isocyanate cross-linking agent are subjected to calendering to obtain the antistatic high-barrier polymer film.

[0021] Firstly, 3,4-ethylenedioxythiophene and 3-thiophene methanol are oxidatively polymerized and deposited on nano-montmorillonite to obtain modified nano-montmorillonite; nano-montmorillonite is a two-dimensional inorganic nano-material, which can form a physical barrier in the antistatic high-barrier polymer film, so that the diffusion process of the penetrating molecules produces a tortuous effect, prolongs the diffusion path, and gives the antistatic high-barrier polymer film excellent barrier properties; the copolymer obtained by copolymerization of 3,4-ethylenedioxythiophene and 3-thiophene methanol has conductivity, and a conductive polymer layer is formed on the modified nano-montmorillonite, and hydroxyl groups are introduced into the modified nano-montmorillonite, and the hydroxyl groups introduced into the modified montmorillonite are cross-linked and cured with the hydroxyl groups on the polyurethane molecular chain through a closed isocyanate cross-linking agent, and the conductive polymer layer forms a conductive path in the antistatic high-barrier polymer film, and gives the antistatic high-barrier polymer film excellent antistatic properties and mechanical properties.

[0022] Secondly, phenyl dichlorophosphate is reacted with glycidol to obtain epoxidized phenyl phosphate; epoxidized phenyl phosphate is reacted with carbon dioxide to obtain functionalized cyclic carbonate, the functionalized cyclic carbonate is reacted with 1,6-hexanediamine to obtain polyurethane, and phosphorus element and hydroxyl group are introduced into the polyurethane molecular chain; the introduction of phosphorus element can give the antistatic high barrier polymer film excellent flame retardant properties; the hydroxyl group introduced into the polyurethane molecular chain can be cross-linked and cured with the hydroxyl group on the modified nano-montmorillonite through a blocked isocyanate cross-linking agent, thereby giving the antistatic high barrier polymer film excellent mechanical properties. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] An antistatic high-barrier polymer film, the preparation method of the antistatic high-barrier polymer film comprises the following preparation steps:

[0026] (1) Nano-montmorillonite, anhydrous ferric chloride and tetrahydrofuran were mixed in a mass ratio of 1:0.03:8, and ultrasonically treated for 1 hour to prepare a mixed solution; 3,4-ethylenedioxythiophene, 3-thiophene methanol, sodium dodecyl sulfate and deionized water were mixed in a mass ratio of 1:0.1:2:6 to prepare a monomer solution; under the stirring conditions of 20°C and 300 r / min, a monomer solution with a mass of 1 times of the mixed solution was uniformly added dropwise to the mixed solution within 30 minutes, the temperature was raised to 45°C, the stirring reaction was continued for 24 hours, the mixture was filtered, and the mixture was washed with anhydrous ethanol and deionized water for 3 times each, and dried at 5Pa and 50°C for 7 hours to obtain modified nano-montmorillonite;

[0027] (2) Phenyl dichlorophosphate, triethylamine, and tetrahydrofuran were mixed in a mass ratio of 1:0.1:8, and glycidol twice the molar amount of phenyl dichlorophosphate was added dropwise at a uniform rate within 30 minutes at 0°C and 300 r / min under a nitrogen atmosphere, and the temperature was raised to 20°C, and the reaction was continued with stirring for 9 hours, filtered, and dried at 5 Pa and 50°C for 7 hours to obtain epoxidized phenyl phosphate; epoxidized phenyl phosphate and tetrabutylammonium bromide were mixed in a mass ratio of 1:0.01, placed in a high-pressure reactor, and carbon dioxide gas was introduced to maintain the pressure at 1.0 MPa, and the reaction was stirred at 95°C and 300 r / min for 6 hours, and cooled to room temperature to obtain functionalized cyclic carbonate;

[0028] (3) Add functionalized cyclic carbonate and 1,6-hexanediamine to N,N-dimethylformamide (10 times the mass of functionalized cyclic carbonate) at a molar ratio of cyclic carbonate group to amino group of 1:1, add 1,5,7-triazabicyclo[4.4.0]dec-5-ene (0.02 times the mass of functionalized cyclic carbonate), stir and react at 135°C, 300 r / min for 24 hours under nitrogen protection, and dry at 5Pa, 50°C for 6 hours to obtain polyurethane; mix polyurethane, modified nano-montmorillonite, and blocked isocyanate crosslinker at a mass ratio of 1:0.05:0.2, place in a hot melt machine, stir at 180°C, 300 r / min for 20 minutes, and then send to a calender for calendering, set the calender temperature to 150°C, the calender speed to 50 m / min, the pressure to 24 MPa, and stand for 6 hours to obtain an antistatic high barrier polymer film.

[0029] Example 2

[0030] An antistatic high-barrier polymer film, the preparation method of the antistatic high-barrier polymer film comprises the following preparation steps:

[0031] (1) Nano-montmorillonite, anhydrous ferric chloride and tetrahydrofuran were mixed in a mass ratio of 1:0.04:9, and ultrasonically treated for 1.5 hours to prepare a mixed solution; 3,4-ethylenedioxythiophene, 3-thiophene methanol, sodium dodecyl sulfate and deionized water were mixed in a mass ratio of 1:0.15:2.5:7 to prepare a monomer solution; under the stirring conditions of 25°C and 400 r / min, 1.1 times the mass of the monomer solution of the mixed solution was uniformly added to the mixed solution within 30 minutes, the temperature was raised to 50°C, the stirring reaction was continued for 22 hours, the mixture was filtered, and the mixture was washed with anhydrous ethanol and deionized water for 4 times each, and dried at 7.5 Pa and 55°C for 6 hours to obtain modified nano-montmorillonite;

[0032] (2) Phenyl dichlorophosphate, triethylamine, and tetrahydrofuran were mixed in a mass ratio of 1:0.15:9, and glycidol (2.1 times the molar amount of phenyl dichlorophosphate) was added dropwise at a uniform rate within 30 minutes under a nitrogen atmosphere at 1°C and 400 r / min stirring conditions, the temperature was raised to 25°C, the stirring reaction was continued for 8 hours, the mixture was filtered, and the mixture was dried at 7.5 Pa and 55°C for 6 hours to obtain epoxidized phenyl phosphate; epoxidized phenyl phosphate and tetrabutylammonium bromide were mixed in a mass ratio of 1:0.02, placed in a high-pressure reactor, carbon dioxide gas was introduced to maintain the pressure at 1.1 MPa, the mixture was stirred at 100°C and 400 r / min for 5 hours, and the mixture was cooled to room temperature to obtain a functionalized cyclic carbonate;

[0033] (3) Add functionalized cyclic carbonate and 1,6-hexanediamine to N,N-dimethylformamide (11 times the mass of functionalized cyclic carbonate) at a molar ratio of cyclic carbonate group to amino group of 1:1, add 1,5,7-triazabicyclo[4.4.0]dec-5-ene (0.03 times the mass of functionalized cyclic carbonate), stir and react at 140°C, 400 r / min for 23 hours under nitrogen protection, and dry at 6Pa, 55°C for 5 hours to obtain polyurethane; mix polyurethane, modified nano-montmorillonite, and blocked isocyanate crosslinker at a mass ratio of 1:0.06:0.25, place in a hot melt machine, stir at 185°C, 400 r / min for 15 minutes, and then send to a calender for calendering, set the calender temperature to 155°C, the calender speed to 55 m / min, the pressure to 27 MPa, and stand for 5.5 hours to obtain an antistatic high barrier polymer film.

[0034] Example 3

[0035] An antistatic high-barrier polymer film, the preparation method of the antistatic high-barrier polymer film comprises the following preparation steps:

[0036] (1) Nano-montmorillonite, anhydrous ferric chloride and tetrahydrofuran were mixed in a mass ratio of 1:0.05:10, and ultrasonically treated for 2 hours to prepare a mixed solution; 3,4-ethylenedioxythiophene, 3-thiophene methanol, sodium dodecyl sulfate and deionized water were mixed in a mass ratio of 1:0.2:3:8 to prepare a monomer solution; under the stirring conditions of 30°C and 500 r / min, a monomer solution 1.2 times the mass of the mixed solution was uniformly added to the mixed solution within 30 minutes, the temperature was raised to 55°C, the stirring reaction was continued for 20 hours, the mixture was filtered, and the mixture was washed with anhydrous ethanol and deionized water for 5 times each, and dried at 10Pa and 60°C for 5 hours to obtain modified nano-montmorillonite;

[0037] (2) Phenyl dichlorophosphate, triethylamine, and tetrahydrofuran were mixed in a mass ratio of 1:0.2:10, and glycidol (2.2 times the molar amount of phenyl dichlorophosphate) was added dropwise at a uniform rate within 30 minutes at 2°C and 500 r / min under a nitrogen atmosphere, and the temperature was raised to 30°C, and the reaction was continued with stirring for 7 hours, filtered, and dried at 10Pa and 60°C for 5 hours to obtain epoxidized phenyl phosphate; epoxidized phenyl phosphate and tetrabutylammonium bromide were mixed in a mass ratio of 1:0.03, placed in a high-pressure reactor, and carbon dioxide gas was introduced to maintain the pressure at 1.2 MPa, and the reaction was stirred at 105°C and 500 r / min for 4 hours, and cooled to room temperature to obtain functionalized cyclic carbonate;

[0038] (3) Add functionalized cyclic carbonate and 1,6-hexanediamine to N,N-dimethylformamide (12 times the mass of functionalized cyclic carbonate) at a molar ratio of cyclic carbonate group to amino group of 1:1, add 1,5,7-triazabicyclo[4.4.0]dec-5-ene (0.04 times the mass of functionalized cyclic carbonate), stir and react at 145°C, 500 r / min for 22 hours under nitrogen protection, and dry at 7Pa, 60°C for 4 hours to obtain polyurethane; mix polyurethane, modified nano-montmorillonite, and blocked isocyanate crosslinker at a mass ratio of 1:0.07:0.3, place in a hot melt machine, stir at 190°C, 500 r / min for 10 minutes, and then send to a calender for calendering, set the calender temperature to 160°C, the calender speed to 60 m / min, the pressure to 30 MPa, and stand for 5 hours to obtain an antistatic high barrier polymer film.

[0039] Comparative Example 1

[0040] The preparation method of the antistatic high barrier polymer film of Comparative Example 1 is different from that of Example 2 only in step (1), and step (1) is modified as follows: nano-montmorillonite, anhydrous ferric chloride, and tetrahydrofuran are mixed uniformly in a mass ratio of 1:0.04:9, and ultrasonically treated for 1.5 hours to prepare a mixed solution; 3,4-ethylenedioxythiophene, sodium dodecyl sulfate, and deionized water are mixed uniformly in a mass ratio of 1:2.5:7 to prepare a monomer solution; under the stirring conditions of 25°C and 400r / min, a monomer solution 1.1 times the mass of the mixed solution is uniformly added dropwise to the mixed solution within 30 minutes, the temperature is raised to 50°C, the stirring reaction is continued for 22 hours, the mixture is filtered, and the mixture is washed with anhydrous ethanol and deionized water 4 times each, and dried at 7.5Pa and 55°C for 6 hours to obtain modified nano-montmorillonite. The remaining steps are the same as those of Example 2.

[0041] Comparative Example 2

[0042] The difference between the preparation method of the antistatic high barrier polymer film of Comparative Example 2 and Example 2 is that step (1) is not performed, and step (3) is modified as follows: functionalized cyclic carbonate and 1,6-hexanediamine are added to N,N-dimethylformamide with a molar ratio of cyclic carbonate group to amino group of 1:1, and 1,5,7-triazabicyclo[4.4.0]dec-5-ene with a molar ratio of 0.03 times the mass of functionalized cyclic carbonate is added, and the mixture is heated at 140°C and 400r / m under nitrogen protection. in stirring reaction for 23h, drying at 6Pa, 55℃ for 5h, and obtaining polyurethane; polyurethane, nano-montmorillonite, and blocked isocyanate crosslinking agent were mixed uniformly at a mass ratio of 1:0.06:0.25, placed in a hot melt machine, stirred at 185℃, 400r / min for 15min, and then sent to a calender for calendering, setting the calender temperature to 155℃, the calendering speed to 55m / min, the pressure to 27MPa, and standing for 5.5h to obtain an antistatic high barrier polymer film. The remaining steps are the same as in Example 2.

[0043] Comparative Example 3

[0044] The preparation method of the antistatic high barrier polymer film of Comparative Example 3 is different from that of Example 2 in that step (1) is not performed, and step (3) is modified as follows: functionalized cyclic carbonate and 1,6-hexanediamine are added to N,N-dimethylformamide with a molar ratio of cyclic carbonate group to amino group of 1:1, and 1,5,7-triazabicyclo[4.4.0]dec-5-ene with a molar ratio of 0.03 times the mass of functionalized cyclic carbonate is added, and the mixture is heated at 140°C under nitrogen protection. The mixture was stirred at 400 r / min for 23 hours, and dried at 6 Pa and 55° C. for 5 hours to obtain polyurethane; the polyurethane and the blocked isocyanate crosslinking agent were mixed evenly at a mass ratio of 1:0.25, placed in a hot melt machine, stirred at 185° C. and 400 r / min for 15 minutes, and then sent to a calender for calendering, the calender temperature was set to 155° C., the calendering speed was 55 m / min, the pressure was 27 MPa, and the mixture was allowed to stand for 5.5 hours to obtain an antistatic high barrier polymer film. The remaining steps were the same as those in Example 2.

[0045] Comparative Example 4

[0046] The preparation method of the antistatic high barrier polymer film of Comparative Example 4 is different from that of Example 2 only in step (2), and step (2) is modified as follows: 1,4-dichlorobenzene, triethylamine, and tetrahydrofuran are mixed uniformly in a mass ratio of 1:0.15:9, and 2.1 times the molar amount of 1,4-dichlorobenzene is added dropwise at a uniform rate within 30 minutes under the stirring conditions of 1°C and 400r / min in a nitrogen atmosphere, and the temperature is raised to 25°C, and the stirring reaction is continued for 8 hours, filtered, and dried at 7.5Pa and 55°C for 6 hours to obtain epoxidized dichlorobenzene; epoxidized dichlorobenzene and tetrabutylammonium bromide are mixed uniformly in a mass ratio of 1:0.02, placed in a high-pressure reactor, carbon dioxide gas is introduced to maintain the pressure at 1.1MPa, and the reaction is stirred at 100°C and 400r / min for 5 hours, and cooled to room temperature to obtain functionalized cyclic carbonate. The remaining steps are the same as those of Example 2.

[0047] Comparative Example 5

[0048] The preparation method of the antistatic high barrier polymer film of Comparative Example 5 is different from that of Example 2 only in step (3). Step (3) is modified as follows: functionalized cyclic carbonate and 1,6-hexanediamine are added to N,N-dimethylformamide (11 times the mass of the functionalized cyclic carbonate) at a molar ratio of cyclic carbonate group to amino group of 1:1, and 1,5,7-triazabicyclo[4.4.0]dec-5-ene (0.03 times the mass of the functionalized cyclic carbonate) is added. The mixture is stirred at 140 °C under nitrogen protection. ℃, 400r / min stirring reaction for 23h, 6Pa, 55℃ drying for 5h to obtain polyurethane; polyurethane and modified nano-montmorillonite were evenly mixed in a mass ratio of 1:0.06, placed in a hot melt machine, stirred at 185℃, 400r / min for 15min, and then sent to a calender for calendering, setting the calender temperature to 155℃, the calendering speed to 55m / min, the pressure to 27MPa, and allowed to stand for 5.5h to obtain an antistatic high barrier polymer film.

[0049] Test Example 1

[0050] Antistatic performance test

[0051] Test method: Using a Zc-36 type high resistance meter from Shanghai Sixth Electric Meter Factory, with air as the ambient medium, the volume resistivity of the embodiment and the comparative example was measured under a voltage of 100 V. The results are shown in Table 1.

[0052] Table 1

[0053]

[0054] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the antistatic high barrier polymer film prepared in the present invention has good antistatic performance.

[0055] By comparison, the volume resistivity of Examples 1 to 3 is greater than that of Comparative Examples 1 to 3, indicating that 3,4-ethylenedioxythiophene and 3-thiophene methanol are oxidatively polymerized and deposited on nano-montmorillonite to obtain modified nano-montmorillonite; the copolymer obtained by copolymerization of 3,4-ethylenedioxythiophene and 3-thiophene methanol has conductivity, a conductive polymer layer is formed on the modified nano-montmorillonite, and hydroxyl groups are introduced into the modified nano-montmorillonite, the hydroxyl groups introduced into the modified montmorillonite and the hydroxyl groups on the polyurethane molecular chain are cross-linked and cured by a blocked isocyanate cross-linking agent, the conductive polymer layer forms a conductive path in the antistatic high-barrier polymer film, and the antistatic high-barrier polymer film has excellent antistatic properties.

[0056] Test Example 2

[0057] Mechanical properties testing

[0058] Test method: AGS-J electronic material stretching machine was used to test the tensile strength of the embodiment and the comparative example according to JB / T2726-1996. The sample width was 15 mm, the clamp spacing was 100 mm, and the tensile speed was 50 mm / min. The results are shown in Table 2

[0059] Table 2

[0060] Tensile strength(MPa) Tensile strength(MPa) Example 1 76.89 Comparative Example 1 66.64 Example 2 77.23 Comparative Example 2 67.31 Example 3 76.81 Comparative Example 3 65.19 Comparative Example 4 77.55 Comparative Example 5 53.11

[0061] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the antistatic high-barrier polymer film prepared in the present invention has good mechanical properties.

[0062] By comparison, the tensile strength of Examples 1 to 3 is greater than that of Comparative Examples 1 to 3 and Comparative Example 5, indicating that 3,4-ethylenedioxythiophene and 3-thiophene carbinol are oxidatively polymerized and deposited on nano-montmorillonite to obtain modified nano-montmorillonite; and hydroxyl groups are introduced into the modified nano-montmorillonite; phenyl dichlorophosphate is reacted with glycidol to obtain epoxidized phenyl phosphate, epoxidized phenyl phosphate is reacted with carbon dioxide to obtain functionalized cyclic carbonate, functionalized cyclic carbonate is reacted with 1,6-hexamethylenediamine to obtain polyurethane, and hydroxyl groups are introduced into the polyurethane molecular chain; polyurethane, modified nano-montmorillonite, and blocked isocyanate crosslinking agent are calendered to obtain an antistatic high-barrier polymer film; the hydroxyl groups introduced into the polyurethane molecular chain can be cross-linked and cured with the hydroxyl groups on the modified nano-montmorillonite through a blocked isocyanate crosslinking agent, thereby giving the antistatic high-barrier polymer film excellent mechanical properties.

[0063] Test Example 3

[0064] Flame retardant performance test

[0065] Test method: The examples and comparative examples were prepared into standard specimens according to GB / T2406.2-2009, and the limiting oxygen index of the standard specimens was tested. The results are shown in Table 3.

[0066] Table 3

[0067] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 28.3 Comparative Example 1 27.9 Example 2 28.4 Comparative Example 2 27.7 Example 3 27.8 Comparative Example 3 28.1 Comparative Example 4 23.7 Comparative Example 5 27.9

[0068] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the antistatic high-barrier polymer film prepared by the present invention has good flame retardant properties.

[0069] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 4, indicating that phenyl dichlorophosphate is reacted with glycidol to obtain epoxidized phenyl phosphate; epoxidized phenyl phosphate is reacted with carbon dioxide to obtain functionalized cyclic carbonate, the functionalized cyclic carbonate is reacted with 1,6-hexamethylenediamine to obtain polyurethane, and phosphorus is introduced into the polyurethane molecular chain; the introduction of phosphorus can give the antistatic high barrier polymer film excellent flame retardant properties.

[0070] Test Example 4

[0071] Barrier performance testing

[0072] Test method: Referring to the national standard GB / T1037-1988, the water vapor transmission rates of the examples and comparative examples were tested. The results are shown in Table 4.

[0073] Table 4

[0074]

[0075] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 4, it can be found that the antistatic high-barrier polymer film prepared in the present invention has good barrier properties.

[0076] By comparison, the water vapor permeability of Examples 1 to 3 is less than that of Comparative Example 3, indicating that 3,4-ethylenedioxythiophene and 3-thiophene methanol are oxidatively polymerized and deposited on nano-montmorillonite to obtain modified nano-montmorillonite; nano-montmorillonite is a two-dimensional inorganic nanomaterial that can form a physical barrier in the antistatic high-barrier polymer film, causing a tortuous effect in the diffusion process of the penetrating molecules, extending the diffusion path, and giving the antistatic high-barrier polymer film excellent barrier properties.

[0077] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An antistatic high barrier polymer film, characterized in that: The antistatic high barrier polymer film is prepared by reacting epoxidized phenyl phosphate with carbon dioxide to obtain functionalized cyclic carbonate; reacting functionalized cyclic carbonate with 1,6-hexamethylenediamine to obtain polyurethane; and calendering polyurethane, modified nano-montmorillonite, and blocked isocyanate crosslinking agent to obtain the film. The modified nano-montmorillonite is prepared by oxidative polymerization of 3,4-ethylenedioxythiophene and 3-thiophene methanol and then depositing the 3,4-ethylenedioxythiophene and 3-thiophene methanol on the nano-montmorillonite.

2. The antistatic high barrier polymer film according to claim 1, characterized in that: The epoxidized phenyl phosphate is prepared by reacting phenyl dichlorophosphate with glycidol.

3. The antistatic high barrier polymer film according to claim 1, characterized in that: The model of the blocked isocyanate cross-linking agent is VESTAGON B1530.

4. The antistatic high-barrier polymer film according to claim 1, characterized in that: The preparation method of the antistatic high-barrier polymer film comprises the following preparation steps: (1) Mix nano-montmorillonite, anhydrous ferric chloride and tetrahydrofuran in a mass ratio of 1:(0.03-0.05):(8-10), and ultrasonically treat for 1-2 hours to prepare a mixed solution; mix 3,4-ethylenedioxythiophene, 3-thiophene methanol, sodium dodecyl sulfate and deionized water in a mass ratio of 1:(0.1-0.2):(2-3):(6-8) to prepare a monomer solution; under the stirring conditions of 20-30°C and 300-500 r / min, add 1-1.2 times the mass of the monomer solution to the mixed solution at a uniform rate within 30 minutes, heat to 45-55°C, continue stirring to react for 20-24 hours, filter, wash with anhydrous ethanol and deionized water for 3-5 times each, and dry at 5-10 Pa and 50-60°C for 5-7 hours to obtain modified nano-montmorillonite; (2) Phenyl dichlorophosphate, triethylamine and tetrahydrofuran are mixed in a mass ratio of 1:(0.1~0.2):(8~10), and in a nitrogen atmosphere, at 0~2°C, 300~500r / min stirring conditions, 2~2.2 times the molar amount of phenyl dichlorophosphate propylene oxide is uniformly added dropwise within 30 minutes, the temperature is raised to 20~30°C, and the stirring reaction is continued for 7~9 hours, filtered, and dried at 5~10Pa, 50~60°C for 5~7 hours to obtain epoxidized phenyl phosphate; Epoxidized phenyl phosphate and tetrabutylammonium bromide are mixed in a mass ratio of 1:(0.01~0.03), placed in a high-pressure reactor, carbon dioxide gas is introduced to maintain the pressure at 1.0~1.2MPa, and the reaction is carried out at 95~105°C, 300~500r / min, stirring for 4~6 hours, and cooled to room temperature to obtain functionalized cyclic carbonate; (3) Adding functionalized cyclic carbonate and 1,6-hexanediamine to N,N-dimethylformamide (10 to 12 times the mass of the functionalized cyclic carbonate) at a molar ratio of cyclic carbonate group to amino group of 1:1, adding 1,5,7-triazabicyclo[4.4.0]dec-5-ene (0.02 to 0.04 times the mass of the functionalized cyclic carbonate), stirring at 135 to 145°C and 300 to 500 r / min for 22 to 24 hours under nitrogen protection, and drying at 5 to 7 Pa and 50 to 60°C for 4 to 6 hours to obtain polyurethane ; Mix polyurethane, modified nano-montmorillonite and blocked isocyanate cross-linking agent in a mass ratio of 1: (0.05-0.07): (0.2-0.3), place in a hot melt machine, stir at 180-190°C and 300-500r / min for 10-20min, and then send to a calender for calendering. Set the calender temperature to 150-160°C, the calendering speed to 50-60m / min, the pressure to 24-30MPa, and let it stand for 5-6h to obtain an antistatic high-barrier polymer film.

5. The antistatic high-barrier polymer film according to claim 4, characterized in that: The reaction process of the functionalized cyclic carbonate in step (2) is as follows: 。 6. The antistatic high-barrier polymer film according to claim 4, characterized in that: The reaction process of the polyurethane in step (3) is as follows: 。 7. Use of the antistatic high barrier polymer film according to any one of claims 1 to 6 in semiconductor packaging.

Citation Information

Patent Citations

  • Water-based antistatic coating and preparation method thereof

    CN103525266A

  • Preparation method of mildew-resistant polyurethane prepolymer

    CN106397714A